OPTIMALISASI PENGEMBANGAN OBJEK WISATA GLAMPING LEMBAH SURGA MELALUI PENDAMPINGAN KKN TEMATIK UNRAM - Ni Wayan Sri Suliartini; Elfan Hidayat; Irham Nil Ardi; Syam Abi Rama Maolana; Nur Muhammad Fadhullah; Titin Sri Farida Hartati; Riza Sofia; Yulia Kartika; Irmayanti Irmayanti; Nurul Zulqaidah; Elvianah Elvianah; Sophia Maharani Meika Azalia (Universitas Mataram, 2022)
Assistance aims to Glamping of Heaven Valley as a tourist destination is carried out through various work programs. Assistance is carried out from June 20 to August 3, 2022, located in Karang Sidemen Village.Various work programs are carried out in mutual cooperation with partners so that Karang Sidemen Village as a tourist village can provide a peaceful environment and a memorable experience for tourists. This method is also expected to further increase the existence and popularity of the village as a tourist village. Some of the mentoring work programs carried out include cleaning the Glamping of Heaven Valley area to make it look clean and the scenery clear, making and installing information boards, making and installing directions to Glamping of Heaven Valley, and making hand railings around steep areas in Glamping of Heaven Valley. The results of assistance are the achievement of cleaning the Glamping of Heaven Valley area in accordance with the plan, the availability of information boards as a medium for delivering information to the public/community, the availability of road signs as signs (signs) on the side of the road as a marker of the shape of the road, the direction of the road. the road, the speed of the vehicle that must be carried to the Glamping of Heaven Valley, and the presence of hand railing that functions to maintain the safety of visitors in steep/steep locations.